Archaeological approaches to market exchange in ancient societies - Garraty, Christopher P., editor; Stark, Barbara L., editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2010)
Market activities were central to the economies of many ancient societies, yet they have received little research from the archaeological community. Archaeological Approaches to Market Exchange in Ancient Societies is the first book to address the development, change, and organizational complexity of ancient markets from a comparative archaeological perspective. Drawing from historical documents and archaeological records from Mesoamerica, the U.S. Southwest, East Africa, and the Andes, this volume reveals the complexity of ancient market place development and economic behavior in both hierarchical and non-hierarchical societies. Highlighting four principal themes---the defining characteristics of market exchange the recognition of market exchange archaeologically the relationship among market, political, and other social institutions and the conditions in which market systems develop and change---the book contains a strong methodological and theoretical focus on market exchange. Diverse contributions from noted scholars show the history of market exchange and other activities to be more dynamic than scholars previously appreciated. Archaeological Approaches to Market Exchange in Ancient Societies will be of interest to archaeologists, anthropologists, material-culture theorists, economists, and historians.--Book jacket.
Theoretical and methodological overviews. Investigating market exchange in ancient societies: a theoretical review / Christopher P. Garraty -- Detecting marketplace exchange in archaeology: a methodological review / Barbara L. Stark and Christopher P. Garraty -- Case studies. The rise and demise of marketplace exchange among the prehistoric Hohokam of Arizona / David R. Abbott -- A multiscalar perspective on market exchange in the classic-period Valley of Oaxaca / Gary M. Feinman and Linda M. Nicholas -- Origins and development of Mesoamerican marketplaces: evidence from South-central Veracruz, Mexico / Barbara L. Stark and Alanna Ossa -- The rise and fall of market exchange: a dynamic approach to ancient Maya economy / Geoffrey E. Brasswell -- Housing the market: Swahili merchants and regional marketing on the East African coast, seventh to sixteenth centuries AD -- Regional and local market systems in Aztec-period morelos / Michael E. Smith -- Comparative contributions. Labor taxes, market systems, and urbanization in the prehispanic Andes: a comparative perspective / Charles Stanish -- Evaluating casual factors in market development in premodern states: a comparative study, with critical comments on the history of ideas about markets / Richard E. Blanton and Lane F. Fargher -- Finding the mark in the marketplace: the organization, development, and archaeological identifications of market systems / Kenneth G. Hirsh.
The Society for American Archaeology, 72nd, 2007 Annual Meeting, Austin, Texas.
Keywords: Commerce, Prehistoric -- Congresses; Economics, Prehistoric -- Congresses; Indians -- Commerce -- Congresses; Markets -- History -- Congresses; Exchange -- History -- Congresses; Civilization, Ancient -- Congresses